A formação de centros de excelência no setor automobilístico brasileiro - Zorovich, Marcelo Rocha e Silva (2012)
The objective of this project is to verify which factors influence the formation of Centers of Excellence (COEs) in the Brazilian automotive industry. Specifically, the influence of the Innovation, the Business Network, the Technical Network, the Business Context as well as the Acquisition of Technology were analyzed. The proposed methodology was based on a quantitative research, through the application of a Survey along with the suppliers of the automotive industry. The statistical technique of Multiple Linear Regression model was used for data analysis by having the COEs as the dependent variable. Based on 91 questionnaires answered, the results conclude that the activities related to innovation, as well as the Acquisition of Technology and the Business Context contribute to the formation of COEs, rejecting the hypothesis related to the Technical Network and the Business Context in which the companies are inserted in.